Stanovení Lonazolacu v plazmĕ kapalinovou chromatografií s fluorescencní detekcí a aplikace metodiky pri srovnání prípravku Lonazolac-Irritren - Stehlík, P; Hapala, J; Cepeláková, H (Ceskoslovenska farmacie, 1991)
An analytical method was worked out to determine Lonazolac in human plasma based on precipitation of human plasma with a precipitating agent and methanol. This deproteinized plasma was analyzed by liquid chromatography with the use of a reverse phase and fluorimetric detection. The described method is sufficiently sensitive (the limit of detection under 0.1 microgram/ml of plasma) and precise (error of the method = 9%). The precision of the method, recovery from the plasma (100 +/- 3%) and stability in frozen plasma (minimally one month) are presented. Application of the method in a comparison of the newly developed Czechoslovak preparation Lonazolac and the foreign preparation Irritren is shown. Results are documented by the course of the levels of both preparations in dependence on time and principal pharmacokinetic parameters derived from the one-compartmental model.
Keywords: pyrazoly; Female; Adult; dospělí; Anti-Inflammatory Agents, Non-Steroidal; Chromatography, Liquid; Humans; ženské pohlaví; chromatografie kapalinová; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; Pyrazoles; antiflogistika nesteroidní